Sistema de locomoción para discapacitados, automatizado con un procesador myRIO acoplado en una silla de ruedas - Paredes-Larroca, Fabricio-Humberto (2018)
This applied research studies the possibility of developing an automated locomotion system for people with disabilities. This system will enable said people to have freedom of movement, which will improve their quality of life, and will allow them to be included in society in an easier way.